2019
DOI: 10.1107/s2056989019003645
|View full text |Cite
|
Sign up to set email alerts
|

Acridine form IX

Abstract: We report a new polymorph of acridine, C13H9N, denoted form IX, obtained as thin needles by slow evaporation of a toluene solution. The structure was solved and refined from powder X-ray data. The structures of five unsolvated forms were previously known, but this is only the second with one molecule in the asymmetric unit. The melting point [differential scanning calorimetry (DSC) onset] and heat of fusion are 108.8 (3) °C and 19.2 (4) kJ mol−1, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…(a) Stick model of the structure of acridine form IX ( P 2 1 / n , Z ′ = 1) . Shadings as used in Figure .…”
Section: Structures Of Acridine Anhydrate Phasesmentioning
confidence: 99%
See 4 more Smart Citations
“…(a) Stick model of the structure of acridine form IX ( P 2 1 / n , Z ′ = 1) . Shadings as used in Figure .…”
Section: Structures Of Acridine Anhydrate Phasesmentioning
confidence: 99%
“…3 Subsequent studies, prior to our work, have turned up seven anhydrous forms, of which the crystal structures were known of five, and one hydrate. [4][5][6][7][8][9][10][11][12][13][14] Over the years, inconsistent naming of the solid forms has led to confusion in characterizing, distinguishing, and identifying the various solid forms. The nomenclature in this review is consistent with forms identified in the 2019 edition of the Cambridge Crystal Structure Database.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations